Follow the money: Understanding the Latin America and Caribbean mangrove restoration funding landscape to assist organizations and funders in improved social‐ecological outcomes - Kerry E. Grimm; Jessica L. Archibald; Erik Petter Axelsson; Kevin C. Grady (Conservation Science and Practice, 2023)
Abstract Recent attention to mangroves' social‐ecological benefits has increased funding for restoration projects. Despite such proliferation, little is known about the mangrove restoration funding landscape. To examine multiscale funding flows and relationships to restoration organizations and their project characteristics, we analyzed 115 surveys completed by the Caribbean and Latin American project managers. We categorized funder types by scale and type (e.g., International NGO) and projects as supported by in‐country, out‐country, or both funders. We identified relationships between funder type/scale and organization/project characteristics (e.g., size, inclusion of community information), which we illustrate using Sankey diagrams. Most funders were from the Global North (n = 165/275), primarily in the United States (n = 65) or broadly at the international scale (n = 59); however, Mexican funders were also prevalent (n = 35). Projects were mostly funded by out‐country (n = 43), then both (n = 36) and in‐country (n = 26). While similarities existed among funder type/scale and organization/project characteristic trends, notable exceptions existed (e.g., foreign government supported larger projects), which we detail and contextualize. We conclude with recommendations for funders and organizations, which include ways funders can better support projects using best practices (e.g., community engagement) and managed by smaller organizations, as well as ways organizations can better target funding based on their organization and project characteristics.